The Influence of Public Service Quality and Village Employee Performance on the Level of Public Satisfaction in Balai Tongah Koto Village, North Payakumbuh District Payakumbuh City - Mertha Yulia Angelina; Muhammad Ihsan (Cita konsultindo, 2026)
Public service quality is an essential indicator of government performance because it reflects the ability of public institutions to meet citizens' needs and expectations. Community satisfaction is influenced not only by the quality of public services but also by the performance of government employees in delivering those services. Therefore, improving service quality and employee performance is expected to enhance public satisfaction and strengthen public trust in local government. This study aimed to analyze the effect of public service quality and employee performance on community satisfaction at the Balai Tongah Koto Urban Village, North Payakumbuh District, Payakumbuh City. This study employed a quantitative research approach using a survey method. The population consisted of residents who had received public services at the Balai Tongah Koto Urban Village Office. A total of 150 respondents were selected using a quota sampling technique. Data were collected through questionnaires, supported by interviews, observations, and documentation. The collected data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS software. The findings revealed that public service quality has a positive and significant effect on community satisfaction. Likewise, employee performance also has a positive and significant effect on community satisfaction. Simultaneously, public service quality and employee performance significantly influence community satisfaction, indicating that improvements in both aspects contribute to higher levels of public satisfaction. The coefficient of determination further demonstrated that both independent variables provide a substantial contribution to explaining variations in community satisfaction. In conclusion, enhancing public service quality and improving employee performance are crucial strategies for increasing community satisfaction. The findings suggest that local governments should continuously improve service standards, strengthen employee competence and professionalism, and optimize public service systems to achieve better service quality and greater public trust.